INCREASING STUDENTS’S CREATIVE THINKING SKILLS WITH COOPERATIVE LEARNING MODEL TYPE SCRAMBLE ON TRIGONOMETRY - Sindi Kurniawati; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
In learning mathematics, less active participant students like tends to silence and rarely ask. Students' ability to express ideas or constructs is not visible, so their creative thinking skills have not been fully explored. The purpose of this research is to know the improvement of students' creative thinking skill with cooperative learning type scramble model in mathematic learnings on material Trigonometry HOTS oriented for the students of class X Light Vehicles Engineering (LVE)-D Muhammadiyah Vocational High School (SMK Muhammadiyah) 1 Bambanglipuro Bantul District even semester of 2017/2018. This research is a classroom action research. The subjects of this research were students of class X LVE-D, which amounted to 26 students. This research's object is the whole process of cooperative learning model type scramble to improve students' creative thinking. Research conducted two cycles of cycle I and cycle II, each c; consists of 2 meetings. Data were collected using observation methods, interviews, and field notes. The data collection instrument uses observation sheets, interview guides, and test questions. Data analysis techniques in the form of data analysis of observations, data interview, and field notes analysis, test analysis, and triangulation. The result of this research shows that learning by using cooperative type model of scramble can improve students' creative thinking skills in learning mathematics in class X LVE-D SMK Muhammadiyah 1 Bambanglipuro academic year 2017/2018. This is proven from the observation result of students' creative thinking skill in learning every cycle has increased, that is average of observation result percentage of student's creative thinking skill at cycle I 51,41% is in enough criteria, while in cycle II increase bec. In comparison, 09% reached the right criteria. Interviews showed a positive response to the students' creative thinking skills.